ANALISIS PENERAPAN AKUNTANSI LEASING ATAS PEROLEHAN ASET TETAP PADA PT. BANK SULUTGO KANTOR PUSAT - Manginsela, Raynaldi; Saerang, David P. E.; Wokas, Heince R. N. (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
Leasing activities are an alternative financing to obtain fixed assets in supporting the operational activities of a company. PT. Bank SulutGo is a company engaged in financial services (banking) that chooses leasing as one of the ways to obtain fixed assets.This study aims to find out how the application of leasing accounting to the acquisition for fixed assets at PT. Bank SulutGo Head Office based on PSAK No. 30. The research method used is qualitative descriptive.The results of the research show that leasing transactions conducted by PT. Bank SulutGo is classified as a finance lease which at the end of the lease period there is a transfer of asset ownership to PT. Bank SulutGo. The application of leasing accounting to the acquisition for fixed assets at PT. Bank SulutGo has not been fully implemented under PSAK No. 30 concerning leasing accounting.Keywords: Accounting for Leases, PSAK No. 30, Fixed Assets